Taphonomic analysis of archaeomalacological assemblages : shell middens on the northern coast of Santa Cruz (Patagonia, Argentina) - Hammond, Heidi (2014)
This paper proposes a method of studying archaeomalacological assemblages from shell middens, and describes an application of this method in the analysis of remains recovered from systematic excavations at sites located south of the Ría Deseado estuary (northern coast of Santa Cruz Province, Argentina). This methodology aims to isolate taphonomic variables affecting archaeomalacological records to aid identification of the agents and processes involved in shell midden formation and to improve interpretations of the human activities performed at the sites. These analyses are also relevant to paleoenvironmental and paleoecological reconstructions, and to interpretations of site variability through assessments of assemblage integrity and structure.